1990
DOI: 10.1111/j.1399-3054.1990.tb04410.x
|View full text |Cite
|
Sign up to set email alerts
|

Response to osmotic medium and fusicoccin by seeds of radish (Raphanus sativus) in the early phase of germination

Abstract: The effect of increasing osmotic values of the medium (mannitol) on the growth and the response mechanisms of seeds of radish (Raphanus sativus L., cv. Ton do Rosso Quarantino) during the early phase of germination was investigated in the presence or absence of fusicoccin (FC). Decreasing the water potential in the medium inhibited the growth and the evolution of protein synthesis and enhanced H+ extrusion, net uptake of K+ and malic acid synthesis. FC, which stimulates these latter functions, counteracted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…It can be suggested that some complementary factors are necessary for the manifestation of the FC effect. Thus, it was shown that there was a synergism in the stimulating effects of an osmoticum and FC on the proton efflux from the pea internode segments [19], in the Arabidopsis suspension culture [20], as well as during the germination of radish seeds [12]. The above points suggest that osmotic factors, such as high salt concentrations, initiate the manifestation of FC effect; under salt stress, FC affects the ionic balance, and, in particular, increases the ä + / Na + ratio [5].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It can be suggested that some complementary factors are necessary for the manifestation of the FC effect. Thus, it was shown that there was a synergism in the stimulating effects of an osmoticum and FC on the proton efflux from the pea internode segments [19], in the Arabidopsis suspension culture [20], as well as during the germination of radish seeds [12]. The above points suggest that osmotic factors, such as high salt concentrations, initiate the manifestation of FC effect; under salt stress, FC affects the ionic balance, and, in particular, increases the ä + / Na + ratio [5].…”
Section: Discussionmentioning
confidence: 98%
“…Such increase could proceed due to a decrease in the rate of potassium ion efflux, which usually are rapidly secreted in the medium during the first hours of imbibition [12]. An increased potassium content in cells results in an increase in their osmotic potential providing for intense water absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose-6-P was determined by measuring NADP § reduction at 340 nm and 25 ~ as described previously (Cocucci et al, 1990). Reducing sugars were measured by the colorimetric method of Nelson (1944).…”
Section: Determination Of the Levels Of Glucose-6-p Reducing Sugarsmentioning
confidence: 99%
“…Fusicoccin significantly alleviated the salinity-induced germination inhibition in Sporobolus arabicus (Khan and Ungar 2001c), Zygophyllum qatarense (Ismail 1990), but had no effect at higher salinity in Salicornia rubra , Aeluropus lagopoides and Urochondra setulosa (Gulzar and Khan 2002). Cocucci et al (1990) indicated that fusicoccin counteracted the inhibitory effect of a declining water potential in the medium of radish seeds by enhancing H + extrusion and synthesis of malic acid. Fusicoccin has also been shown to affect seed germination by accelerating development and by replacing the requirements for light and endogenous hormones in breaking dormancy (Lado et al 1975).…”
Section: Discussionmentioning
confidence: 97%